The coping strategies among student-athletes who have to let go their academic goal - Omar Fauzee, M.S; Don, Yahya; Daud, Yaakob; Hj. Yaakub, Muhamadul Bakir; Sutresna, Nina; Abdullah, Nagoor Meera (HRMARS, 2014)
The main purpose of this study was to examine the relationship of the coping strategy and level of representations of student-athletes at university level. More specifically, it also investigates the relationship of high school level of sport representations and university level of sport representation. A sample of 307 (female-213; male-94) university students-athletes in one of the public university in Malaysia were randomly selected for this study. The age of the student- athletes (M=22.09, sd=1.35 Out of the number, 210 represented college dormitory, 51 represented university at National level, and 46 represented state at national level, and 6 representing Nation at International level. The Athletic Coping Skills Inventory – 28 was used to measure the psychological coping skills for athletes. The instrument consisted of a 28-item scale measuring seven classes of sport-specific psychological coping skills including confidence, goal setting, coping with adversity, freedom from worry, coachability, concentration, peaking under pressure, and goal setting. Results shows that all of the seven coping strategies were significantly correlated with the four level of university representations. The major findings found that a high correlation between the goal setting and confidence level of the athletes. Another findings also found that the goal setting and confidence level also moderately correlated with coping with adversity. However, a weak relationship was found between high chool sports representation and university level of sports representations. Results were further discussed and suggestions for future research also suggested in this paper.